Pentingnya Pendampingan Belajar Literasi dan Numerasi Bagi Siswa Sekolah Dasar Kelas Rendah - Maria Erlinda; Alexandro De Jesus; Romana Rozaria Maia; Plaudius Januari Wago; Maria Novensia Tia; Maria Damaris Berek; Kristina Beso Jawan (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
The MBKM (Free Learning Independent Campus) activity is an activity that is required for every student at the Faculty of Teacher Training and Education, Widya Mandira Catholic University, Kupang, to disseminate new knowledge and gain factual experiences from the place where field activities are carried out, in order to improve the teacher competency of prospective students. Teacher. MBKM activities outside of class are carried out through community service. Community service is carried out through literacy and numeracy learning assistance activities for lower grade elementary school students in Liliba Village RT 39, RW 11, Oebobo District, Kupang City, East Nusa Tenggara Province. Learning assistance activities aim to improve literacy and numeracy skills. This community service method uses community service activities in the form of learning support activities for lower grade elementary school students which are participated in by students in grades 1-3. The results of this research show that literacy is going well and there is good development in literacy and numeracy skills.